ANALISIS FUNGSI DAN PEMANFAATAN TAMAN TEMATIK MELALUI MEDIA SOSIAL TWITTER - Ramadhan, Fitrah
The function suitabilities between the thematic park and the needs of its users are the key to make the the thematic park more sustainable. To create a thematic park that is able to accommodate the needs of its users, a communicative planning process is needed which can involve and accommodate the needs of the users. But to execute this process is difficult thing, because not all communities can provide input to that planning process. The presence of social media, especially Twitter as a forum for social networking, can push the community to express their aspirations. From this Twitter, community needs for thematic parks can be seen and can be used as input for planning and evaluation. The city of Bandung makes thematic parks as a main program to increase the people happiness index. The suitability between the theme park's function and the needs of its users must be evaluated to see whether the park is sustainable or not. Therefore, this study is conducted with the aim to identifying the level of suitability between the functions formed by the local government and the utilization patterns reflected in Twitter social media related to thematic parks in Bandung. This research uses a descriptive method with a qualitative approach. Based on analysis, both the function and the formation of utilization, each park has its own characteristics. However, if it viewed from the side of suitability, there are 13 out of 29 parks where there is a mismatch between the function and the form of utilization that is reflected on Twitter social media.